Diálogos asimétricos. Una propuesta de análisis de la imagen romántica de España - Xavier Andreu-Miralles (Amnis)
The article outlines the utility of applying a Bakhtinian philosophy of language and some ideas from postcolonial criticism to the transnational study of national stereotypes, which have been until now specially and fruitfully analyzed by Imagology. It synthetically presents some results of applying these perspectives for the study of the “romantic myth” of Spain and its relevance for the understanding of Spanish nation-building process.